PERKEMBANGAN KEDUDUKAN PEREMPUAN DALAM HUKUM ADBALI (Studi di Kota Denpasar) - Ni Nyoman Sukerti (University of Udayana, 2014)
Women as citizens of the ancients is still received discriminatory treatment in someaspects of life, although the government has made some rules that provide protection towomen evens have ratified CEDAW. The Constitution also been set in Article 27, paragraphs1 and 2, but discrimination against women still exist, especially in the traditional law of Baliinheritance. On the basis of the two problems posed namely 1). Against wealth whose positiondaughter suffered developments in traditional law of Bali heritance? and, 2). What factorsinfluence the occurrence of the development of women position in traditional law of Baliheritance ? Results of the research showed that inherited asset is generally daughter disposableproperty rich guna kaya. Varied forms of inherited property have fixed things as well asmoving objects. Rights received largely daughter also vary greatly between the cases of theother cases, this depends of the economic condition of her parents. Daughter of position heirsare not burdened family responsibilities. So, the position of the daughter of experience in thedevelopment of traditional law of Bali heritance limited -use property rich guna kaya .Factors that influence the occurrence of the development of women position in traditional law of Bali heritance, the availability of legislation that gender perspective, there is aparadigm shift in attitude and behavior of the parents of the girls looked, viability of publiceducation level and economy growing family.